Communicative ecology of hajj pilgrims and its impact on perceived satisfaction with the services provided by the Saudi government - Fazal Rahim Khan (Tanjong Malim, 2019)
Communicative ecology of hajj pilgrims and its impact on perceived satisfaction with the services provided by the Saudi government by Fazal Rahim Khan